Literasi Digital dalam Rangka Peningkatan Kemampuan Manajemen Keuangan Keluarga bagi Ibu-ibu Rumah - Lisa Martiah Nila Puspita (Abdi Reksa, 2021)
Family financial management and control practices have received little attention. This absence can lead to bigger problems in a family. However, if the family finances have been well planned and managed, every member of the family will feel serenity in his house. By taching the housewives about the urgency of financial management and technical guidance of existing family financial management applications, the financial problems faced will be easier to anticipate in advance. If this problem can be resolved by every family, then the goal of a prosperous family can be realized. This program aims to explain the urgency of family financial management and provide technical guidance using an Android-based financial management application for housewives in Muara Bangkahulu sub-district, Bengkulu city. The results show that these housewives have a better understanding of the urgency of family financial management and skills in using family financial management applications by using their handphones after join this program.